Genus Journal of Population Sciences - Egidi, Viviana
GENUS - Journal of Population Sciences - is an open access peer-reviewed journal published by Springer on behalf of the Sapienza University of Rome. Founded in 1934 by Corrado Gini, GENUS has adopted an interdisciplinary approach to population studies. It has an interdisciplinary focus by publishing articles of “pure” demography and articles aiming to further a better knowledge of the interrelationship between demography and biological, social and economic phenomena, connected with the evolution of the population. These have spanned not only pure demography but also anthropology and anthropometric, sociology and psychology, biology and genetics. In keeping with the times -and particularly from 1965 under Nora Federici, and from 1993 under Antonio Golini as directors – an increasing number of articles have been published on general population theories, population dynamics and mathematical demography. GENUS has always tried to promote open dialogue across cultural, ideological and at times theoretical walls in the attempt to understand the complexities underlying population issues.